Flow of compassion in healthcare: moving beyond an individual towards a systemic focus - Tierney, S; Seers, K; Reeve, J; Tutton, L (Royal College of Nursing, 2017)
Compassion is an underpinning construct in nursing, an ideal that is a motivating force for those working in healthcare. Nevertheless, delivering compassionate care (CC) is not always easy or achieved. Little research has investigated how it is enacted and what it means to healthcare professionals (HCPs).